Knowledge, Attitude, and Practice Towards PMTCT of HIV/AIDS among HIV-Positive Mothers in PHC Minna, Niger State - Addakano Bello Umar; Ismaila Abubakar Waziri; Zulkiflu Argungu; Salihu Abdulrahman Kombo; Sani Mohammad Sani (Nursing and Health Sciences Journal (NHSJ), 2024)
Mother-to-child transmission (MTCT) of HIV may occur during pregnancy, labor, and after childbirth, with 10–15% of the highest risks during breastfeeding. This problem is significant in the Sub-Saharan African countries, of which Nigeria is inclusive, where more than 80% of children living with HIV are found, with over 10,000 new pediatric HIV infections per year and a 26.9% MTCT transmission rate in 2017. Thus, this study assesses the knowledge, attitude, and practice towards PMTCT of HIV. A cross-sectional descriptive survey design was employed for the study, a multistage sampling method with a proportional allocation of samples to each Primary Health Care Center, and systematic simple random sampling were used to select 175 study participants. The Instrument for data collection was a self-administered questionnaire developed by the researchers based on the study objectives guided by previous studies, the instrument was pilot-tested and had a reliability Cronbach alpha coefficient of 0.738. Data collected were analyzed using SPSS version 25.0, descriptive statistics were used to describe the frequency distribution and are presented using frequency tables and percentages. The study finding shows that the respondent’s level of knowledge is high (62.6%), the attitude was positive (3.1), and practice was good (70.2%) towards the prevention of mother-to-child transmission (PMTCT) of HIV respectively. In this study, the respondents' level of knowledge was good, their attitude was positive, and their practice was good for PMTCT of HIV. This finding also reveals that healthcare providers are doing a good job in providing counseling sessions and knowledge of PMTCT to pregnant women attending antenatal care. Though, much is needed to increase their acceptance and use of PMTCT for HIV services.